2011
DOI: 10.1080/15287394.2011.618973
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Micro RNA-146a (miRNA-146a), A Marker for Inflammatory Neurodegeneration, in Sporadic Creutzfeldt–Jakob Disease (sCJD) and Gerstmann–Straussler–Scheinker (GSS) Syndrome

Abstract: A mouse- and human-brain-abundant, nuclear factor (NF)-κB-regulated, micro RNA-146a (miRNA-146a) is an important modulator of the innate immune response and inflammatory signaling in specific immunological and brain cell types. Levels of miRNA-146a are induced in human brain cells challenged with at least five different species of single- or double-stranded DNA or RNA neurotrophic viruses, suggesting a broad role for miRNA-146a in the brain’s innate immune response and antiviral immunity. Upregulated miRNA-146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 41 publications
4
100
1
Order By: Relevance
“…The prediction result was verified based on recent experimental literatures. As a result, in the top 3 potential related miRNA list predicted by RLSMDA for 32 diseases investigated here, 34 disease-miRNA associations were successfully confirmed by biological experiments636465666768697071727374757677787980818283848586878889909192939495 (See Table 3). …”
Section: Resultsmentioning
confidence: 55%
“…The prediction result was verified based on recent experimental literatures. As a result, in the top 3 potential related miRNA list predicted by RLSMDA for 32 diseases investigated here, 34 disease-miRNA associations were successfully confirmed by biological experiments636465666768697071727374757677787980818283848586878889909192939495 (See Table 3). …”
Section: Resultsmentioning
confidence: 55%
“…Lukiw recently reported that an upregulated miRNA-146a might be integral to innate immune or inflammatory brain cell responses in prion-mediated infections and to progressive and irreversible neurodegeneration of both the murine and human brain [23]. Although accumulated evidence suggests that miRNA-146a may participate in SCI recovery [5, 8, 24], there is still limited knowledge of the miRNA-146a regulatory networks that modulate genes expression.…”
Section: Discussionmentioning
confidence: 99%
“…LED-Northern dot blots are a significant advancement over classical Northern blotting techniques because they utilize LNA-stabilized miRNAs or anti-miRNAs(AMs) covalently linked to a nylon-based membrane matrix (using EDC) and are probed using DIG-labeled small RNAs with fluorescent reporters [1922]. miRNA and/or AMs, as locked nucleic acid (LNA) oligonucleotides, included a control miRNA-183 (5′-TATGGCACTGGTAGAATTCACT-3′), anti-miRNA-155 (AM-155; 5′-AATTACGATTAGCACTATCCCCA-3′), and a scrambled control AM-155 (AM-155sc; 5′-TTAACATTAGACGATATCCCACC-3′) were purchased from Applied Biosystems/Ambion, Austin, Texas, USA or Exiqon Inc., Woburn, Massachusetts, USA [11,16], and were used at a 5–20 nM ambient concentration that was replenished at every change of ABM (see above; Lonza, Basel, Switzerland) for a total treatment time of 12 and 36 h after the induction of TNF-α + Aβ42 peptide. miRNA-146a and AM-146a sequences and their usage have been described previously [1217].…”
Section: Methodsmentioning
confidence: 99%